An Acute Transverse Myelitis Attack after Total Body Irradiation: A Rare Case. (24th July 2013) - Keklik, Muzaffer; Kaynar, Leylagul; Yildirim, Afra; Sivgin, Serdar; Eroglu, Celalettin; Cingoz, Serife; Pala, Cigdem; Eser, Bulent; Cetin, Mustafa; Unal, Ali
Abstract : Total body irradiation (TBI) combined with chemotherapy is widely used as a pretreatment regimen of bone marrow transplantation (BMT) in hematologic disorders. Late complications related to TBI as part of the conditioning regimen for hematopoietic stem cell transplantation have been revealed. Acute transverse myelitis (ATM) is a neurological syndrome characterized by disorder of motor, sensorial, and autonomic nerves, and tracts at medulla spinalis, which is resulted from involvement of spinal cord. In this paper, we presented an ATM attack developed after TBI in a patient with acute lymphoblastic leukemia (ALL) as it is a rarely seen case.